Iron-based anode catalyst for direct ammonia solid oxide fuel cell
Ti4+ doped La0.7Sr0.3Fe1-xTixO3-δ anode material was prepared by the sol-gel method and composited with Ce0.8Sm0.2O1.9 oxide, which solved the problem of taking into account both the stability and catalytic activity of the anode catalyst in the prior art, and achieved efficient and stable catalytic performance and long-term stability.
Patent Information
- Application Number
- CN202510336623.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-06-20
AI Technical Summary
The existing direct ammonia solid oxide fuel cell anode catalyst is difficult to take into account both stability and catalytic activity, and there are phase decomposition problems, which affects long-term stability and catalytic performance.
The La0.7Sr0.3Fe1-xTixO3-δ anode material was prepared by the sol-gel method. Through Ti4+ doping and Ce0.8Sm0.2O1.9 oxide composite, the electronic conductivity and ionic conductivity of the material were improved to form an efficient and stable anode catalyst.
The high stability of the material under a reducing atmosphere is achieved, phase decomposition is avoided, catalytic activity and output performance are improved, especially under ammonia conditions, it exhibits a power density comparable to hydrogen, and has good long-term stability.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of preparation of anode catalysts for solid oxide direct ammonia fuel cells, and particularly relates to the preparation and application of an iron-based anode catalyst for a high-efficiency and stable direct ammonia solid oxide fuel cell. Background Art
[0002] The use of traditional fossil fuels will emit a large amount of carbon dioxide, sulfides, and nitrogen oxides, triggering a series of problems such as the greenhouse effect, environmental pollution, and energy shortage. This makes people urgently develop renewable energy or other new energy sources. As a green and environmentally friendly energy conversion device, a solid oxide fuel cell can convert chemical energy into electrical energy without being restricted by the Carnot cycle, and its energy utilization efficiency can reach 60-80%; the all-solid electrolyte can avoid the problem of electrolyte leakage and is safer; in addition, it has a wide range of fuel selectivity and strong adaptability, and can convert fuel into electrical energy more flexibly. Ammonia, as a fuel that does not contain carbon and is rich in hydrogen (17.6 wt%), is one of the most synthesized industrial chemicals globally. Due to its high volumetric energy density and low carbon emission characteristics, combined with lower transportation costs than hydrogen, it is gradually being used as an energy source in the field of fuel cells. Therefore, the anode is crucial for the catalysis of ammonia. The traditional composite nickel-based metal anode Ni-YSZ shows good catalytic activity for the oxidation of H2 and NH3, but nitrogen oxides need to be removed from the gas after the electrochemical process. However, due to the high interfacial energy of Ni, metallic Ni may coarsen and migrate, resulting in the shortening of the electrochemically active triple phase boundary and severely reducing the output performance. The perovskite iron-based anode has the application potential to avoid the above problems and also has considerable advantages in terms of price cost. However, most iron-based materials will have a problem of phase decomposition in a reducing atmosphere, which may have some adverse effects on stability; if the stability of the material is to be ensured, it may limit the precipitation of metal nanoparticles, resulting in a decrease in catalytic activity. To sum up, designing an anode catalyst with a simple preparation process, good long-term stability, high catalytic activity and utilization rate for ammonia is an inevitable and important problem for direct ammonia solid oxide fuel cells. Summary of the Invention
[0003] The core purpose of the present invention is to propose an efficient and stable iron-based anode catalyst for a direct ammonia solid oxide fuel cell and its preparation method in view of the existing problems of the prior art. The aim is to improve the catalytic performance of the anode of the direct ammonia solid oxide fuel cell for ammonia fuel gas, achieve high utilization rate, high output performance, and excellent redox stability. The sol-gel method is used to prepare La 0.7 Sr 0.3 Fe 1-x Ti x O 3-δAn anode material, the process of this method is simple, energy consumption is low, and the synthesized material has good uniformity, so as to solve the problem that the existing stability and catalytic activity cannot be well balanced.
[0004] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0005] A preparation method of a highly efficient and stable iron-based anode catalyst for a direct ammonia solid oxide fuel cell, comprising the following steps:
[0006] (1) Weigh lanthanum nitrate hexahydrate, strontium nitrate, and iron salt in a beaker according to the stoichiometric ratio, dissolve with deionized water and stir for 1 hour. Weigh ethylenediaminetetraacetic acid with a molar ratio of 1:1 to metal ions in another beaker and dissolve it in 5–10 mL of ammonia water. Mix the solutions in the two beakers and continue stirring to obtain solution A.
[0007] (2) Measure the stoichiometric amount of titanium source and drop it into the beaker, then add 10–20 mL of absolute ethanol for dissolution. Weigh ethylenediaminetetraacetic acid with a molar ratio of 1:1 to metal ions in another beaker and dissolve it in 5–10 mL of ammonia water. Mix the solutions in the two beakers and continue stirring to obtain solution B.
[0008] (3) Add a complexing agent with a molar ratio of 1:1.5 to metal ions to solution A and solution B respectively, and stir well for 1 hour to dissolve it. Then add the B mixed solution drop by drop into the A solution with a constant pressure funnel at a speed of 2–5 seconds / drop. At this time, some white precipitates will be generated in the solution. After the dropping is completed, continue to adjust the pH value to 6–7 with ammonia water until the white precipitates in the solution disappear;
[0009] (4) Heat the A and B mixed solutions in a water bath at a temperature maintained at 70–90 °C for 4–6 hours. Wait until the solvent is evaporated and the solution becomes a transparent sol state. Put the obtained sol into an oven and dry it at 150–180 °C for 12–24 hours to obtain a precursor gel.
[0010] (5) Take out the precursor gel and let it cool naturally, grind it from a block into a powder, and put it into a high-temperature muffle furnace for roasting to obtain a precursor powder.
[0011] (6) The obtained precursor powder is reduced under a hydrogen / argon mixed gas with a hydrogen flow rate of 50–100 mL / min to obtain the anode material.
[0012] (7) Preparation of anode slurry
[0013] Mix La 0.7 Sr 0.3 Fe 1-x Ti x O 3-δ Anode and Ce0.8 Sm 0.2 O 1.9 Mix in a ratio of 3:2 by mass, then add 2 - 6 drops of a viscous agent solution containing 4% - 8% pore former and continue grinding for 30 - 60 minutes until the powder and the solution are evenly mixed to obtain a pretreated anode paste.
[0014] Furthermore, the iron salt in step (1) is one or more of ferric nitrate nonahydrate, ferric chloride, ferrous sulfate heptahydrate, and iron acetate.
[0015] Furthermore, the titanium source in step (1) is one or more of tetrabutyl titanate, isopropyl titanate, ethyl titanate, and titanium tetrachloride.
[0016] Furthermore, the molar ratio of the metal ions described in steps (1) and (3) to ethylenediaminetetraacetic acid is 1:0.8 - 1, and the molar ratio of the metal ions to citric acid is 1:1 - 2.
[0017] Furthermore, the complexing agent selected in step (3) is one or more of citric acid, glycine, oxalic acid, tartaric acid, and salicylic acid.
[0018] Furthermore, the calcination process in step (5) is as follows: pre - calcine at 400 - 600 °C for 5 - 8 hours, control the heating rate at 2 - 5 °C / min, then carry out calcination at 1000 - 1100 °C for 2 - 5 hours, and maintain the heating rate at 2 - 5 °C / min.
[0019] Furthermore, the hydrogen content in the hydrogen / argon mixed gas introduced into the tubular furnace in step (6) is 10 vol% - 50 vol%, and the reduction time at 800 °C is 5 - 10 hours.
[0020] Furthermore, the viscous agent in step (7) is one or more of terpineol, pine oil, polyvinyl alcohol, polyethylene glycol, and acrylic resin.
[0021] Furthermore, in step (7), mix La 0.7 Sr 0.3 Fe 1-x Ti x O 3-δ with Ce 0.8 Sm 0.2 O 1.9 in a mass ratio of (4 - 6):(6 - 4).
[0022] The beneficial effects of the present invention are as follows:
[0023] (1) The Ti 4+ doping La 0.7 Sr 0.3 FeO 3-δfor preparing La with single perovskite structure 0.7 Sr 0.3 Fe 1- x Ti x O 3-δ , this material, compared with its doped matrix La 0.7 Sr 0.3 FeO 3-δ and most iron-based perovskites, can be highly stable in a reducing atmosphere without phase decomposition.
[0024] (2) Ti 4+ As a high-valence ion with variable valence, the Ti 4+ / Ti 3+ transition in the perovskite lattice provides good electronic conductivity. The composite phase formed by combining with Ce 0.8 Sm 0.2 O 1.9 oxide compensates for the deficiency of ionic conductivity, thus obtaining a material with generally high conductivity.
[0025] (3) Under the test conditions of pure hydrogen and pure ammonia, this material has good catalytic activity. The power density obtained under ammonia conditions is comparable to that under hydrogen, and the repeatability is good, indicating that ammonia can replace hydrogen as a new clean energy under appropriate catalytic action. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD patterns of La 0.7 Sr 0.3 Fe 1-x Ti x O 3-δ (0.1 ≤ x ≤ 0.4) samples before and after reduction;
[0027] Figure 2 SEM comparison diagrams of La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ samples before and after reduction;
[0028] Figure 3 Stability diagram of La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ sample as the anode operating under ammonia for 100 hours. DETAILED DESCRIPTION OF THE INVENTION
[0029] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.
[0030] Example 1
[0031] (1) Single perovskite La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ Synthesis of oxides
[0032] According to the stoichiometric ratio, weigh 3.031 grams of lanthanum nitrate hexahydrate, 0.6349 grams of strontium nitrate, and 3.232 grams of ferric nitrate nonahydrate in a beaker, and add 200 mL of deionized water to dissolve. Then weigh 5.5526 grams of ethylenediaminetetraacetic acid in another beaker, add ammonia water until it is completely dissolved, pour the ammonia water dissolved in ethylenediaminetetraacetic acid into the above salt solution, stir for 1 hour, and record it as solution A. Take another beaker, add 0.6804 grams of tetrabutyl titanate, and then add 10 mL of anhydrous ethanol to dissolve, then add ammonia water dissolved in 0.2922 grams of ethylenediaminetetraacetic acid to the beaker, stir for 1 hour, and record it as solution B. Then add citric acid with a molar ratio of metal ion: complexing agent = 1:1.5 to solutions A and B, and stir until dissolved. Then, the flow rate was controlled by a constant pressure funnel, and solution B was slowly added to solution A. The pH value of the mixed solution was adjusted to 6-7 with ammonia water. There was no obvious white precipitate in the solution. The mixed solution was heated in a water bath, and the temperature was maintained at 80°C for 5 hours. After the solvent evaporated, the heating was stopped, and the sol was placed in an oven at 180°C for 12 hours to obtain a dry gel. The block of dry gel was taken out, ground into powder in an agate mortar, and then pre-calcined at 600°C in a crucible for 5 hours, and then heated to 1100°C and calcined for 5 hours to obtain La with good crystallinity. 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ The precursor powder was reduced under 50% H2 / Ar at 50 mL / min and 800 °C for 10 hours to obtain La with active Fe nanoparticles on the surface. 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ (LSFT82) Perovskite anode catalyst.
[0033] (2) Anode slurry preparation
[0034] La 0.7 Sr 0.3 Fe 0.8Ti 0.2 O 3-δ The anode and Ce 0.8 Sm 0.2 O 1.9 First, import them into an agate mortar according to the mass ratio of 3:2 and grind for 10 minutes for preliminary mixing. Then add 3 - 5 drops of a thickening agent with the mass ratio of ethyl cellulose: turpentine alcohol = 4:96, and continue grinding for 30 minutes until there is no obvious granular feeling and the slurry shows a smooth and viscous state, then stop grinding. Obtain La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ and Ce 0.8 Sm 0.2 O 1.9 composite anode slurry.
[0035] (3) Product performance testing
[0036] For battery preparation, YSZ with a diameter of 15 mm is used as the electrolyte support, La 1-x Sr x MnO 3-δ -YSZ composite slurry is used as the cathode, and La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ -SDC is used as the anode slurry. The specific process is as follows: First, screen-print the anode slurry (with a diameter of 10 mm and an effective area of 0.785 square centimeters) on one side of the electrolyte and put it in an oven at 60 °C for drying. Then brush the cathode slurry (with a diameter of 5 mm and an effective area of 0.196 square centimeters) on the other side of the electrolyte. After drying, bake it in a high-temperature furnace for 2 hours to make the electrode and the electrolyte combine more tightly, obtaining La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ -SDC∣YSZ∣La 1-x Sr x MnO 3-δ -YSZ single cell. Before testing, coat a thin layer of silver paste on the electrode by screen printing as the current collector layer.
[0037] The assembly process of the battery test device is as follows: First, place a silver wire with a diameter of 0.5 mm and a length of 50 mm and a nickel mesh with a diameter of 15 mm on the corundum tube of the test device. Then, attach the anode side of the prepared battery slice to the nickel mesh, and place a silver mesh and a silver wire above the cathode side in sequence. Apply a little platinum paste between the components to increase contact, and finally seal it with high-temperature ceramic glue. During the test, introduce high-purity ammonia as the fuel gas, and use a Zahner IM6 type electrochemical workstation to test the current-voltage curve and impedance spectrum.
[0038] Example 2
[0039] The specific preparation method is basically the same as that of Example 1, except that the synthesis of La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ is changed to the synthesis of La 0.7 Sr 0.3 Fe 0.9 Ti 0.1 O 3-δ 3.232 grams of ferric nitrate nonahydrate is changed to 3.636 grams, and 0.6806 grams of tetrabutyl titanate is changed to 0.3403 grams.
[0040] Example 3
[0041] The specific preparation method is basically the same as that of Example 1, except that the synthesis of La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ is changed to the synthesis of La 0.7 Sr 0.3 Fe 0.7 Ti 0.3 O 3-δ 3.232 grams of ferric nitrate nonahydrate is changed to 2.828 grams, and 0.6806 grams of tetrabutyl titanate is changed to 1.021 grams.
[0042] Example 4
[0043] The specific preparation method is basically the same as that of Example 1, except that the synthesis of La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ is changed to the synthesis of La 0.7 Sr 0.3 Fe 0.6 Ti 0.4 O 3-δFor the synthesis, change 3.232 g of iron(III) nitrate nonahydrate to 2.424 g, and change 0.6806 g of tetrabutyl titanate to 1.361 g.
[0044] Example 5
[0045] The specific preparation method is basically the same as that of Example 1, except that iron(III) nitrate nonahydrate is changed to iron(III) chloride.
[0046] Example 6
[0047] The specific preparation method is basically the same as that of Example 1, except that tetrabutyl titanate is changed to titanium(IV) chloride.
[0048] Example 7
[0049] The specific preparation method is basically the same as that of Example 1, except that citric acid is changed to glycine.
[0050] Example 8
[0051] The specific preparation method is basically the same as that of Example 1, except that the molar ratio of metal ion: complexing agent = 1:1.5 is changed to 1:1.2.
[0052] Example 9
[0053] The specific preparation method is basically the same as that of Example 1, except that the molar ratio of metal ion: complexing agent = 1:1.5 is changed to 1:1.
[0054] Example 10
[0055] The specific preparation method is basically the same as that of Example 1, except that the solvent anhydrous ethanol of tetrabutyl titanate is changed to acetone.
[0056] Example 11
[0057] The specific preparation method is basically the same as that of Example 1, except that the volume of deionized water for dissolving nitrate is changed from 200 mL to 250 mL.
[0058] Example 12
[0059] The specific preparation method is basically the same as that of Example 1, except that the pH value of the solution is adjusted from 7 to 6.
[0060] Example 13
[0061] The specific preparation method is basically the same as that of Example 1, except that the pH value of the solution is adjusted from 7 to 8.
[0062] Example 14
[0063] The specific preparation method is basically the same as that of Example 1, except that the temperature of water bath heating is changed from 80 °C to 70 °C.
[0064] Example 15
[0065] The specific preparation method is basically the same as that of Example 1, except that the temperature of water bath heating is changed from 80 °C to 90 °C.
[0066] Example 16
[0067] The specific preparation method is basically the same as that of Example 1, except that the drying temperature of the sol is adjusted from 180 °C to 150 °C.
[0068] Example 17
[0069] The specific preparation method is basically the same as that of Example 1, except that the drying temperature of the sol is adjusted from 180 °C to 165 °C.
[0070] Example 18
[0071] The specific preparation method is basically the same as that of Example 1, except that the reducing gas in the tubular furnace is changed from 50% H2 / Ar to 10% H2 / Ar.
[0072] Example 19
[0073] The specific preparation method is basically the same as that of Example 1, except that the reduction time in the tubular furnace is changed from 10 hours to 5 hours.
[0074] Example 20
[0075] The specific preparation method is basically the same as that of Example 1, except that the calcination temperature and time of the sample are changed from 1100 °C, 5 hours to 1100 °C, 2 hours.
[0076] Comparative Example 1
[0077] La 0.7 Sr 0.3 FeO 3-δ Synthesis of Anode Catalyst
[0078] According to the stoichiometric ratio, weigh 3.031 g of lanthanum nitrate hexahydrate, 0.6349 g of strontium nitrate, and 4.04 g of ferric nitrate nonahydrate into a beaker, and add 200 mL of deionized water to dissolve. Then weigh 5.8448 g of ethylenediaminetetraacetic acid into another beaker, add ammonia water until it is completely dissolved, pour the ammonia water dissolved with ethylenediaminetetraacetic acid into the above salt solution, stir for 1 hour, then add citric acid to the solution with a molar ratio of metal ion: complexing agent = 1:1.5, stir until dissolved, and adjust the pH value of the mixed solution to 6-7 with ammonia water. Heat the solution in a water bath, keep the temperature at 80°C, and maintain the time for 5 hours. Stop heating after the solvent evaporates, and bake the sol in an oven at 180°C for 12 hours to obtain a dry gel. The block of dry gel was taken out, ground into powder in an agate mortar, and then pre-fired in a crucible at 600℃ for 5 hours, and then heated to 1100℃ for 5 hours to obtain La with good crystallinity. 0.7 Sr 0.3 FeO 3-δ (LSF) precursor powder.
[0079] Comparative Example 2
[0080] The specific implementation method is basically the same as Example 1 of this section, except that the anode catalyst is replaced with a commercial nickel oxide catalyst.
[0081] Table 1 Current density and power density of direct ammonia solid oxide fuel cell at 800℃
[0082]
[0083]
[0084] for Figure 1 From the XRD pattern of a, we can see that the synthesized materials all have hexagonal single perovskite structure, which is similar to La 0.6 Sr 0.4 FeO 3-δ The standard card matches well, indicating that La can be successfully synthesized according to the method of the present invention 0.7 Sr 0.3 Fe 1- x Ti x O 3-δ Single perovskite structure oxides. Figure 1 b XRD pattern shows that the reduced La 0.7 Sr 0.3 Fe 1-x Ti x O 3-δ Still maintain the original structure, indicating that Ti 4+ Doping into the lattice can indeed maintain the stability of the structure. Figure 2From the SEM images before and after reduction, it can be seen that after reduction, the Fe particles are firmly anchored on the surface of the perovskite matrix and are evenly distributed, which can provide better catalytic activity and conductivity. Figure 3 Using La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ as the anode, the stability curve of discharging at 100 mA / cm 2 for 100 hours shows that there is no obvious attenuation of the battery during long-term operation, indicating that the anode has the potential for long-term stable operation.
[0085] From the data in Table 1, it can be seen that the peak power densities of La 0.7 Sr 0.3 Fe 0.9 Ti 0.1 O 3-δ , La 0.7 Sr 0.3 Fe 0.8 Ti 0.2 O 3-δ , La 0.7 Sr 0.3 Fe 0.7 Ti 0.3 O 3-δ , La 0.7 Sr 0.3 Fe 0.6 Ti 0.4 O 3-δ as the anode are 306, 368, 265, and 246 mW / cm 2 . Appropriate doping of Ti 4+ can improve the electrochemical performance of the anode material, and the output power is about 1.5 times that of LSF and 4.6 times that of traditional NiO. It shows that Ti 4+ is a feasible solution for constructing an efficient and stable iron-based anode catalyst.
[0086] The above are only the preferred embodiments of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention shall fall within the scope of the present invention.
Claims
1. An iron-based anode catalyst for a direct ammonia solid oxide fuel cell, characterized in that: Take La 0.7 Sr 0.3 Fe 1- x Ti x O 3-δ, , 0.1≤x≤0.4, 0<δ<1 is a carrier, and the surface of the carrier is loaded with Fe nanoparticles in the composite catalyst.
2. A method for preparing the iron-based anode catalyst for direct ammonia solid oxide fuel cell according to claim 1, characterized in that: The following steps are involved: (1) Dissolve lanthanum, strontium nitrate and iron salt in deionized water, dissolve ethylenediaminetetraacetic acid in ammonia water, and mix the two solutions to obtain solution A. (2) Place the titanium source in anhydrous ethanol and stir to dissolve it. Take ethylenediaminetetraacetic acid and completely dissolve it in ammonia water. Mix the two solutions evenly to obtain solution B. (3) Adding a complexing agent to solution A and solution B, respectively, to obtain solution A1 and solution B1, then adding solution B1 dropwise to solution A1, and adjusting the pH value with aqueous ammonia until the white precipitate in the solution disappears, to obtain solution C; (4) Stirring solution C in a water bath and evaporating it to dryness, and drying it at 150–180 °C for 12–24 hours to obtain a precursor gel; (5) Cooling, grinding, and calcining the precursor gel to obtain an anode catalyst precursor; (6) Reducing the anode catalyst precursor powder in a hydrogen / argon mixed gas to obtain the anode catalyst.
3. The method according to claim 2, characterized in that: In step (1), the iron salt is one or more of ferric nitrate nonahydrate, ferric chloride, ferrous sulfate heptahydrate, and ferric acetate; and the molar ratio of the metal ion to ethylenediaminetetraacetic acid is 1:0.8–1.
4. The method according to claim 2, characterized in that: In step (2), the titanium source is one or more of tetrabutyl titanate, isopropyl titanate, ethyl titanate, and titanium tetrachloride.
5. The method according to claim 2, characterized in that: In step (3), the complexing agent is one or more of citric acid, glycine, oxalic acid, tartaric acid, and salicylic acid, and the molar ratio of the metal ion to the complexing agent is 1:1-2.
6. The method according to claim 2, characterized in that: In step (5), the calcination process is: pre-calcination at 400-600 °C for 5-8 hours, controlling the heating rate to 2-5 °C / min, and calcination at 1000-1100 °C for 2-5 hours.
7. The method according to claim 2, characterized in that: In step (6), the hydrogen content in the hydrogen / argon mixed gas is 10-50 vol%; the reduction temperature is 800 °C, and the time is 5-10 hours.
8. A use of the iron-based anode catalyst for a direct ammonia solid oxide fuel cell according to claim 1 or the iron-based anode catalyst for a direct ammonia solid oxide fuel cell prepared by the method according to any one of claims 2 to 7, characterized in that: The anode catalyst is prepared into an anode slurry as an anode material for a direct ammonia solid oxide fuel cell; the anode slurry is prepared by: preparing the anode catalyst La 0.7 Sr 0.3 Fe 1-x Ti x O 3-δ With Ce 0.8 Sm 0.2 O 1.9 The mixture is mixed and ground for 20-60 minutes, and a thickener solution containing 4-8 wt.% of a pore former is added, and the mixture is further ground until the mixture is uniformly mixed to obtain an anode slurry.
9. The use according to claim 8, characterized in that: La 0.7 Sr 0.3 Fe 1-x Ti x O 3-δ With Ce 0.8 Sm 0.2 O 1.9 The mass ratio is 4–6:6–4.
10. The use according to claim 8, characterized in that: The viscous agent is one or more of turpentine alcohol, terpineol, polyvinyl alcohol, polyethylene glycol, and acrylic resin.